Base-metal catalysts based on porous layered double hydroxides for alkaline-free sodium borohydride hydrolysis. (3rd August 2017) - Mostajeran, Mehdi; Prévot, Vanessa; Mal, Sib S.; Mattiussi, Emily; Davis, Boyd R.; Baker, R. Tom
Abstract: Catalyzed hydrolysis of sodium borohydride (SBH) has demonstrated promise for generation of a pure hydrogen stream for use with fuel cells. In designing an improved continuous hydrogen generator that uses the substantial heat released in the hydrolysis reaction to more effectively separate the sodium borate by-product, we sought a robust base-metal catalyst that could tolerate the exothermic reaction under flow conditions. Working under base-free conditions in ethanol solvent we identified reduced nickel and iron-containing particles supported on layered double hydroxides (LDHs) as robust catalysts. Catalytic activity was enhanced further using high surface area hierarchical supports prepared using the ' inverse opal ' method. In particular, macroporous NiMgAl and FeMgAl LDHs produced 0.4 and 1.0 mol of hydrogen per minute per mole of active metal of the supported catalyst in aqueous ethanol solvent. Graphical abstract: Highlights: Base-free hydrolysis of borohydride in ethanol for use in portable H2 generator. Supported layered double hydroxide (LDH) catalysts are active in ethanol solvent. Catalyst activity is enhanced in hierarchical inverse-opal LDH materials.